إشكالية بناء الوضعية الادماجية لدى تلاميذ الطور الابتدائي - دادوش, مريم; هدار, إلهام (مكتبة كلية الأدب العربي والفنون, 2023)
تناول هذا البحث الحديث عن نشاط التعبير الكتابي وعن الوضعية الإدماجية، فاهتمامنا بهذا النشاط ، دفعنا إلى الاهتمام بطريقة تدريس نشاطات اللغة العربية في المنهاج، والهدف من ذلك معرفة مكانة اللغة العربية في المدرسة الجزائرية، وطريقة تدريسها خاصة في هذا نشاط ، الذي هو وسيلة من الوسائل الموجهة لخدمة اللغة وتعزيز الاستعمال اللغوي الصحيح. إن تدريس هذا النشاط جاء وفق ما سطره المنهاج،الذي اعتمد على المقاربة النصية كمنطلق أساسي لتنمية مهارات التعبير وإدماج معارف وخبرات المتعلمين فيه، لمواجهة مختلف الصعوبات التي تواجههم في حياتهم، حيث يعتبر التعبير الكتابي والوضعية الإدماجية الوعاء الذي تصب فيه كل نشاطات اللغة العربية ،ومن خلالهما يتحقق الإدماج الفعلي للمعارف وبه تتحقق وظيفة التواصل،فالوضعيةالإدماجية أشمل وأوسع من التعبير الكتابي في توظيف مكتسبات التي سبق وأن تعلمها التلميذ خلال مقطع واحد أو عدة مقاطع This research talks about The activity of Writing Expression and the Situation of Integration. Our focusing on the activity of the writing expression motivated us to make an importance for the method of teaching of Arabic language activities in the methodology in order to the importance of the Arabic language in the Algerian school and the manner of its teaching especially in writing expression which is one of the means oriented to serve the language and improve a right linguistic usage. The teaching of this activity is according to the methodology that depends on Textual-based approach as the main step for developing in it skills of the expression and integrating of experiences and knowledge of learners to face against several problems in their life. The writing expression and the situation of the integration are considered as the main place that gathers all of Arabic language activities. Both of them make the real integration of knowledge and the function of communication. The situation of integration has huge signification than writing expression in using acquirements learned by pupil before through one or more piece
السنة الثالثة أنموذجا
Keywords: التعبير الكتابي،الوضعيةالإدماجية ،المنهاج،الكفاءات; Book cscpression , incremental, the curriculum ,competencies